Getting our ACT together. Issue 3 (15th June 2015) - Gore, Katrina; Stanley, Phil
<x xml:space="preserve">Abstract</x> Results that cannot be replicated during drug trials cost pharma companies millions. Katrina Gore and Phil Stanley describe a tool developed by Pfizer to improve the quality of preclinical study design and analysis